Discharging of dust particles of different sizes in an argon afterglow plasma - Denysenko, I.B.; Mikikian, M.; Azarenkov, N.A. (Problems of Atomic Science and Technology, 2022)
The dust charge distribution function (DCDF) in an argon plasma afterglow is obtained by solving numerically the master equation describing dust discharging as a one-step stochastic process. The calculated DCDFs are compared with Gaussian distributions, and it is found that the dust charge distribution functions can be approximated quite well by the latter ones for different external conditions. It is found how the DCDF, mean dust charge, variance and charging time depend on dust size. For late afterglow times, it is also analyzed how the emission of electrons in the collisions of excited argon atoms with dust particles affects the DCDF. It is shown that the emission effect is more essential for larger nanoparticles than for smaller ones. Здобуто функцію розподілу порошинок за зарядом (ФРПЗ) у післясвітінні аргонової плазми шляхом числового розв’язання основного кінетичного рівняння, що описує розрядження порошинок як однокроковий стохастичний процес. Розраховані ФРПЗ порівняно з розподілами Гаусса, і виявлено, що останні можуть доволі добре описувати функції розподілу порошинок за зарядом за різних зовнішніх умов. З’ясовано, як ФРПЗ, середній заряд порошинок, дисперсія функції Гаусса, що апроксимує ФРПЗ, та час заряджання порошинок залежать від розміру порошинок. Для пізніх часів післясвітіння також аналізується, як емісія електронів у зіткненнях збуджених атомів аргону з порошинками впливає на ФРПЗ. Показано, що вплив цієї емісії на більші порошинки є більш суттєвим, ніж на малі.